Neuroprotective Effect of Artesunate in Experimental Model of Traumatic Brain Injury - Gugliandolo, Enrico; D'Amico, Ramona; Cordaro, Marika; Fusco, Roberta; Siracusa, Rosalba; Crupi, Rosalia; Impellizzeri, Daniela; Cuzzocrea, Salvatore; Di Paola, Rosanna (Frontiers in Neurology, 2018)
Traumatic brain injuries (TBI) are an important public health challenge, in addition, subsequent events at TBI can compromise the quality of life of these patients. In fact, TBI is associated with several complications both long and short term, some evidence shows how TBI is associated with a decline in cognitive functions such as the risk of developing dementia, cerebral atrophy, and Parkinson disease. After the direct damage from TBI, a key role in TBI injury is played by the inflammatory response and oxidative stress, that contributing to tissue damage and to neurodegenerative processes, typical of secondary injury, after TBI. Given the complex series of events that are involved after TBI injury, a multitarghet pharmacological approach is needed. Artesunate is a more stable derivative of its precursor artemisin, a sesquiterpene lactone obtained from a Chinese plant Artemisia annua, a plant used for centuries in traditional Chinese medicine. artesunate has been shown to be a pluripotent agent with different pharmacological actions. therefore, in this experimental model of TBI we evaluated whether the treatment with artesunate at the dose of 30mg \ Kg, had an efficacy in reducing the neuroinflammatory process after TBI injury, and in particular in inhibiting the NLRP3 inflammosome pathway, which plays a key role in the inflammatory process. we also assessed whether treatment with artesunate was able to exert a neuroprotective action by modulating the release of neurotrophic factors. our results show that artesunate was able to reduce the TBI-induced lesion, it also showed an anti-inflammatory action through the inhibition of Nf-kb, release of proinflammatory cytokines IL-1 and TNF- and through the inhibition NLRP3 inflammosome complex, furthermore reduce the activation of astrocytes and microglia (GFAP, Iba-1). finally, our results show that the protective effects of artesunate also occur through the modulation of neurotrophic factors (BDNF, GDNF, NT-3) which play an important role in neuronal survival.